2011
DOI: 10.1111/j.1872-034x.2011.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Case of severe liver damage after the induction of tocilizumab therapy for rheumatoid vasculitis

Abstract: A 71-year-old male patient was diagnosed with rheumatoid arthritis (RA) in 2000. Various disease-modifying anti-rheumatic drugs (DMARDs) and an anti-tumor necrosis factor biologic etanercept were administrated, but were unable to control the disease activity of RA. He was then diagnosed with rheumatoid vasculitis and received a total of 3 courses of an anti-interleukin-6 receptor antibody, tocilizumab. After the 3 courses of tocilizumab therapy, ascites and renal dysfunction gradually appeared and he was admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…Liver test abnormalities have been documented within the TCZ clinical trials (category A/D evidence156 163 165 174 176 181 182 199 203 204 220–222). Cases have been reported of TCZ-induced hepatic failure (category D evidence223). …”
Section: Tocilizumab (Il-6 Inhibition)mentioning
confidence: 99%
“…Liver test abnormalities have been documented within the TCZ clinical trials (category A/D evidence156 163 165 174 176 181 182 199 203 204 220–222). Cases have been reported of TCZ-induced hepatic failure (category D evidence223). …”
Section: Tocilizumab (Il-6 Inhibition)mentioning
confidence: 99%
“…Mahamid et al and Hiura et al reported each a case with rather sub acute evolution over months leading in the first case to histological focal pericentral vein hepatocellular necrosis and steatosis [ 14 ]. In the second one, of note a lethal case, marked liver atrophy and ascites were observed with no focal necrosis but mild inflammatory cell infiltration and little periportal fibrosis at histology [ 15 ]. Interestingly, liver enzymes were normal or only slightly elevated, and supplementary immunohistochemical analysis in the second case revealed a high amount of cleaved caspase 3 antigen positive hepatocytes, suggesting rather apoptosis than necrosis at the origin of liver injury [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the second one, of note a lethal case, marked liver atrophy and ascites were observed with no focal necrosis but mild inflammatory cell infiltration and little periportal fibrosis at histology [ 15 ]. Interestingly, liver enzymes were normal or only slightly elevated, and supplementary immunohistochemical analysis in the second case revealed a high amount of cleaved caspase 3 antigen positive hepatocytes, suggesting rather apoptosis than necrosis at the origin of liver injury [ 15 ]. The authors hypothesized that the poor outcome could be due to IL-6 inhibition, a cytokine involved with liver regeneration [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bei einer großen Untersuchung ist dies in 0,06 von 100 Patientenjahren der Fall [21]. Leichte Transaminasenanstiege sind häufig, aber auch schwere Hepatitiden sind unter den berichteten Zwischenfällen [22,23]. Für den B-Zelldepletor Rituximab und den T-Zell-Kostimulationshemmer Abatacept wurden bisher keine schweren Leberreaktionen publiziert, das letztere wurde sogar als Ausweichpräparat bei Adalimumab-induzierter Hepatitis vorgeschlagen [24].…”
Section: Leflunomid (Lef)unclassified